2020 Director's Report of Research in Kansas - J. E. Minton (Kansas Agricultural Experiment Station Research Reports, 2023)
The Director’s Report of Research in Kansas includes a list of journal articles, station publications, and other published manuscripts from scientists in our departments, research-extension centers, and associated programs.
Keywords: Kansas Agricultural Experiment Station; land-grant; agricultural research; experiment station; life sciences; veterinary sciences